Raising external logistics industry in Europe: a systemic vision of the economic approach - Flavio Boscacci; Giulia Pesaro (European Regional Science Association (ERSA), 2002)
This paper proposes a new systemic approach to the analysis of the External Logistics Industry (or Third Party Logistics) as well as a discussion on the interactions between logistics activities and the territory. The recent evolution of this economic field represents an obvious consequence of the widespread reorganisation of the manufacturing industry and his changing demand in term of supply chain management. The new analytic model developed allows to aggregate all different logistic services providers into four categories, on the basis of some common features. It permits to compact the definition of the different types of providers and, through this, to define the shape of the new industry. According to the proposed new dynamic approach to the logisic sector, also the interactions system between the economic actors and the territorial elements and functions is likely to change. The evolution of the logistics firms, regarding roles, objectives, organisation models and strategies, implies an evolution in the use of land, infrastructures and collective environmental and territorial resources. Such a framework allows some interesting considerations along two main dimensions: the first concerns with the rules that should guide economic and public actors action on territory (which means also the need to identify the instruments to reduce the negative environmental externalities); the second ones estimate the territorial impacts regarding the infrastructures for the mobility and the linked land services. REFERENCES: - Boscacci F., Pesaro G. (2001), Indagine sull'evoluzione strutturale delle imprese della logistica in Italia, Assologistica, Milano. - Ottimo E., Vona R. (2001), Sistemi di logistica integrata. Hub territoriali e logistica internazionale, Egea, Milano. - Senn L., Boscacci F. (1999), I luoghi della trasformazione e dell'innovazione, Edizioni Seat, Torino.
Keywords: 330